Crystallization kinetics, polymorphism fine tuning, and rigid amorphous fraction of poly(vinylidene fluoride) blends. Issue 5 (18th August 2021) - Govinna, Nelaka Dilshan; Sadeghi, Ilin; Schick, Christoph; Asatekin, Ayse; Cebe, Peggy
Abstract: Fast scanning calorimetry (FSC) is used to study crystallization of poly(vinylidene fluoride) (PVDF), and its blends with a random fluorinated copolymer (FCP) of poly(methyl methacrylate) and 1H, 1H, 2H, 2H‐perfluorodecyl methacrylate (PMMA‐ r ‐PFDMA). By varying the residence time at isothermal melt crystallization temperatures T MC  = 80–120°C, the amount of α‐ and β‐phase can be controlled, yielding partial or complete suppression of β‐phase for all blends studied. Nonisothermal crystallization kinetics are also studied by FSC and analyzed using the Mo model. Crystallization rates increase when FCP is present. PVDF crystallizes into β‐phase when cooled from the melt at rates faster than 3000 K/s giving PVDF crystal fractions of about 0.05–0.16. Only α‐phase occurs at cooling rates slower than 2000 K/s yielding larger PVDF crystal fractions of about 0.30–0.43. Cooling rates between those limits result in mixed α‐ and β‐phase. The rigid amorphous fraction (RAF) of PVDF varies with α and β crystal fraction in PVDF/FCP blends. RAF of α‐phase PVDF ranges from 0.21 to 0.28 whereas RAF of β‐phase PVDF spans a wider range, reaching values from 0.42 to 0.46. Abstract : Poly(vinylidene fluoride) (PVDF) is an industrially relevant polymer with interesting crystallization behavior. Fast scanning calorimetry is used to study crystallization of PVDF blended with a random fluorinated copolymer. The crystalline polymorphs are controlled through cooling rate and/or the crystallization time and temperature. At fast cooling rates PVDF and its blends crystallize primarily into the polar beta phase with a large amount of rigid amorphous phase around the crystals, possibly due to their needle‐like form.